Therapeutic Efficacy of Liposomal Rifabutin in a Mycobacterium avium Model of Infection - Gaspar, Maria Manuela (American Society for Microbiology, 2000)
Liposomal formulations of rifabutin were developed, and the effects of some parameters on the incorporation efficiency were studied. The antimycobacterial activity of rifabutin incorporated into liposomes prepared with phosphatidylcholine and phosphatidylserine (molar ratio, 7:3) was evaluated in a murine model of infection with a virulent Mycobacterium avium strain (strain P1581) and was compared with that of free rifabutin. The influences of the size of the liposomal rifabutin formulation, the administered doses, and the treatment schedules on the evolution of infection were studied. Two types of treatment schedules were assayed: therapeutic and prophylactic. The therapeutic treatment started 2 weeks after infection, while the prophylactic treatment began 1 day before the experimental infection with mycobacteria. Incorporation of rifabutin in liposomes resulted in a significant enhancement of activity against M. avium infection compared to that of rifabutin in the free form in both schedules. These results demonstrate that liposomal formulations of antibiotics such as rifabutin may be effective for the treatment or prophylaxis of infectious diseases.